ANALISIS NILAI TAMBAH KACANG SANGRAI PADA UD. TARSIUS DI DESA KINNALI KECAMATAN KAWANGKOAN - Rizky ., Manueke; Juliana R. Mandei; Paulus A. Pangemanan (Sam Ratulangi University, 2016)
This research aims to see the difference in value and value added of a product, after experiencing processing in a production process. In the processing of Value Added can be defined as the difference between the value of the product with the cost of raw materials and other inputs not including labor. This Study for to calculate the value 1 kg of raw nuts to 0.73 bean roaster. This research will be implemented since March until June 2016 at UD. Tarsius in Kinali Village, Kawangkoan Sub-district, Minahasa District The data collection includes primary data and secondary data. The primary data obtained through direct interviews with owners of industrial processing of roasted peanuts and employee, as well as direct observation in place research. Secondary data were obtained from various literature related with this study. Research shows that Value Added obtained For 1 kg of raw nuts be roasted peanuts 0.73 that is Rp. 4.105,41 and Value Added to 0.73 bean roaster be roasted beans that have been packaged that is Rp. 6.169,5.*jrm*